Associations of maternal inflammatory states with human milk composition in mothers of preterm infants - Landau-Crangle, Erin; O’Connor, Deborah; Unger, Sharon; Hopperton, Kathryn; Somerset, Emily; Nir, Hadar; Hoban, Rebecca (Frontiers in Nutrition, 2024)
Overweight/obesity (ow/ob) is increasing in prevalence in pregnant women and is associated with other pro-inflammatory states such as pre-eclampsia, gestational diabetes, and preterm labor. Data are lacking if mothers experiencing inflammatory states who deliver preterm have mother’s own milk (MOM) with differing inflammatory markers or pro-inflammatory fatty acid (FA) profiles. The aim was to explore associations of maternal pre- and perinatal inflammatory states with levels of inflammatory markers and/or FAs in longitudinal samples of MOM from mothers of preterm infants born <1250g. Inflammatory states included pre-pregnancy overweight/obesity (ow/ob), diabetes, chorioamnionitis (chorio), preterm labor (PTL), premature rupture of membranes (PROM), pre-eclampsia, caesarian delivery. In MOM, inflammatory markers studied included C-reactive protein [CRP], free choline, IFN-Ɣ, IL-10, IL-1β , IL-1ra, IL-6, IL-8, TNF-α; and FAs included omega-6:omega-3 ratio, arachidonic acid [ARA], docosahexaenoic acid [DHA], linoleic acid, monounsaturated FAs, and saturated FAs. The above inflammatory states were assessed individually as well as the most common states groupedhealthiest mothers (normal BMI, no chorio, +/- no pre-eclampsia) grouped. Regression analysis tested associations at baseline (day 5) and over time using generalized estimating equations. 92 infants were included who delivered to mothers (42% ow/ob) at median gestational age 27.7 weeks and birth weight 850g. MOM CRP was 116% higher (relative change odds ratio [OR] 2.16) in mothers with ow/ob at baseline compared to others (p=0.01) and lower (relative changeOR 0.46, 0.33, respectively) in mothers in the 2 “healthy groups” at baseline (both p<0.05) compared to others. MOM IL-8 levels were lower with chorio and PTL at baseline. No significant associations were found for other individual or grouped inflammatory states nor for other MOM inflammatory markers nor FA profiles at baseline. In conclusion, MOM CRP levels are positively associated with inflammatory states such as ow/ob. Reassuringly, there was no association between FA profiles or most other inflammatory markers and maternal inflammatory states. Further studies are needed to determine potential associations or ramifications of MOM CRP in vulnerable preterm infants.